Cardiotoxicity and Cardioprotection by Artesunate in Larval Zebrafish - Chuanrui Zheng; Letian Shan; Peijian Tong; Thomas Efferth (SAGE Publishing, 2020)
Although artesunate (ART) is generally accepted as a safe and well-tolerated first-line treatment of severe malaria, cases of severe side effects and toxicity of this compound are also documented. This study applied larval zebrafishes to determine the acute toxicity and efficacy of ART and performed RNA-sequencing analyses to unravel the underlying signaling pathways contributing to ART's activities. Results from acute toxicity assay showed that a single-dose intravenous injection of ART from 3.6 ng/fish (1/9 maximum nonlethal concentration) to 41.8 ng/fish (lethal dose 10%) obviously induced pericardial edema, circulation defects, yolk sac absorption delay, renal edema, and swim bladder loss, indicating acute cardiotoxicity, nephrotoxicity, and developmental toxicity of ART. Efficacy assay showed that ART at 1/2 lowest observed adverse effect level (LOAEL) exerted cardioprotective effects on zebrafishes with verapamil-induced heart failure. Artesunate significantly restored cardiac malformation, venous stasis, cardiac output decrease, and blood flow dynamics reduction. No adverse events were observed with this treatment, indicating that ART at doses below LOAEL was effective and safe. These results indicate that ART at low doses was cardioprotective, but revealed cardiotoxicity at high doses. RNA-sequencing analysis showed that gene expression of frizzled class receptor 7a ( fzd7a ) was significantly upregulated in zebrafishes with verapamil-induced heart failure and significantly downregulated if ART at 1/2 LOAEL was coadministrated, indicating that fzd7a -modulated Wnt signaling may mediate the cardioprotective effect of ART. For the first time, this study revealed the biphasic property of ART, providing in-depth knowledge on the pharmacological efficacy-safety profile for its therapeutic and safe applications in clinic.